2018
DOI: 10.2471/blt.17.199679
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic distribution channels in Thailand: results of key-informant interviews, reviews of drug regulations and database searches

Abstract: Objective To analyse how antibiotics are imported, manufactured, distributed and regulated in Thailand. Methods We gathered information, on antibiotic distribution in Thailand, in in-depth interviews – with 43 key informants from farms, health facilities, pharmaceutical and animal feed industries, private pharmacies and regulators– and in database and literature searches. Findings In 2016–2017, licensed antibiotic distribution in Thailand inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…Practices of farmers on antibiotics utilization, showed that the purchase of antibiotics overthe-counter and without prescription was prevalent amongst farmers in the study area. This was consistent with assertions that antibiotics can easily be bought without prescription in some developing countries [29]. Even if there is prescription, it is usually invalid or issued by unlicensed veterinarians [29].…”
Section: Discussionsupporting
confidence: 85%
“…Practices of farmers on antibiotics utilization, showed that the purchase of antibiotics overthe-counter and without prescription was prevalent amongst farmers in the study area. This was consistent with assertions that antibiotics can easily be bought without prescription in some developing countries [29]. Even if there is prescription, it is usually invalid or issued by unlicensed veterinarians [29].…”
Section: Discussionsupporting
confidence: 85%
“…The inappropriate antimicrobial use by pastoralists might be linked with this ease of access and inadequate advice for farmers (35). Restricting access to antimicrobials by removing over-the-counter sales has been identified as a potential route to better antimicrobial use in animals (6,36).…”
Section: Discussionmentioning
confidence: 99%
“…Poor awareness of AMR has been identified as a hurdle to changing antimicrobial practices in many low-and middle-income countries [38,39]. Overall, study respondents had a poor knowledge of what defined AMR and expressed few concerns over the impact of AMR on either human or animal health.…”
Section: Policy and Social Drivers Of Antimicrobial Usementioning
confidence: 94%
“…At present, there are many questions over the capacity and economic feasibility of enforcing antimicrobial use policy in Indonesia; it is useful to draw on the experiences of neighbouring countries. For example, despite Thailand having a more extensive infrastructure and tighter control over antimicrobials, researchers have identified that the illegal use of antimicrobials in livestock may be widespread [39,50]. In order to minimise the risks of antimicrobials becoming a black-market commodity, a stepwise approach to regulation would be best taken in Indonesia.…”
Section: Policy and Social Drivers Of Antimicrobial Usementioning
confidence: 99%
See 1 more Smart Citation